Applications of Nanotechnology for Combating Drug Resistant Bacterial Infections Using Nanoparticles - Kassab, Mohammed Ali (Universitas Muhammadiyah Sidoarjo, 2025)
Background: The global rise of antibiotic-resistant bacteria presents a significant threat to public health, necessitating alternative antimicrobial strategies. Specific Background: Nanoparticles such as silver (AgNPs), zinc oxide (ZnO-NPs), and copper oxide (CuO-NPs) have emerged as promising agents due to their broad-spectrum antibacterial properties. Knowledge Gap: However, comparative data on their efficacy across different resistance levels and their underlying mechanisms, particularly oxidative stress induction, remain limited. Aim: This study aims to evaluate the antibacterial efficacy of AgNPs, ZnO-NPs, and CuO-NPs against 150 bacterial isolates categorized into high-, moderate-, and non-resistant bacteria (HRB, MRB, NRB). Results: AgNPs exhibited the highest overall antibacterial activity, with the greatest average zone of inhibition (26.28 mm for MRB) and the lowest MIC/MBC values (7.89 µg/mL for NRB). CuO-NPs produced the highest reactive oxygen species (ROS), suggesting a distinct mechanism of oxidative damage, while ZnO-NPs showed moderate effectiveness. Statistical analyses (ANOVA, Tukey HSD, Pearson’s r) confirmed significant differences among nanoparticles and a strong correlation between ROS generation and bacterial inhibition for CuO-NPs. Novelty: This is among the few studies providing a comprehensive comparison of these nanoparticles across graded resistance levels. Implications: The findings highlight AgNPs' potential in combating resistant bacteria and underscore the need for further research on their long-term safety and integration into antimicrobial therapies.Highlight : AgNPs most effective: Silver nanoparticles showed the highest antibacterial activity across all resistance levels (HRB, MRB, NRB). ROS production matters: CuO-NPs generated the most reactive oxygen species, contributing to bacterial cell damage. Dual mechanisms: Nanoparticles act via oxidative stress and membrane disruption, enhancing their antibacterial potency. Keywords : Nanotechnology, Bacterial Infection, Resistant Bacteria, MRSA